GENDER EQUALITY IN ONLINE ENGLISH BOOK IN READING AND WRITING MATERIALS - Nurhaedah Gailea; Awey Mulyana (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2020)
This study is to find out whether the writing and reading material is gender biased in the online English book published by British Council. The researchers used qualitative method by using content analysis technique. The data are collected through document review. The research focused on the analysis of six aspects which suggested by Logsdon, they were number of female/male in character, in the linguistic Equal on she and he as pronouns, one’s profession, gender role and behaviors, female and male on which focus on public and domestic role, female and male which focus on art talent, sport ability, and intellectual competence in art and sport in online English book. The result of research showed that the percentage of female is higher than male in the aspects female pronouns in writing material, gender roles (public role) in reading material, art, and sport talent in both of reading and writing material. And the percentage of male are higher than female in the aspects male characters in reading material, female pronouns in reading material and intellectual competence in reading material. It can be concluded that online English books written by the British Council are still found with inequality gender.